Traditional Game as the Communication in Disaster Mitigation - Siti Khadijah, Ute Lies; Rizal, Edwin; Sri Rejeki, Diah; M Hadian, Sapari; Khairul Anwar, Rully (International Journal of Psychosocial Rehabilitation, 2019)
Indonesia is included in the ring of fire zone; a disaster could happen without advance warning and place. The fact is, in 2018, there were 513 disasters that happened, such as tornadoes or puting beliung, landslides, forest fires, floods, earthquakes, and eruptions. Like what had happened in Maluku, due to the extreme weather, there were floods and landslides in several spots in Ternate, North Maluku. To see that, it is considered very important to give early education about how to resolve the disaster. For example, the elementary student through the traditional game. Traditional games are one of the educational instruments that can be used to deliver messages for learning purposes. The goal of this research is to know that the traditional game is able to deliver how to resolve the disaster. Research method, which is used qualitatively through deep interview, focus group discussion, and field observation. The research results are (1) kinds of traditional games, the function, and how to use them suitable with the culture of the North Maluku community. (2) Through the traditional game, the students learn knowledge about how to resolve the disaster in a fun way. The conclusion of this research is that traditional game can give education to the elementary students about how to resolve the disaster